2013
DOI: 10.1155/2013/871929
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aurora a Kinase Expression in Breast Cancer: A Tool for Early Diagnosis?

Abstract: Aurora A kinase is overexpressed in many cancers but the status of this protein in the breast cancer often varies. We investigate the expression and localization of Aurora A protein in relation with tumor emergence and progression in breast cancer. Aurora A kinase status was evaluated in 107 patients using immunohistochemistry. The experimental findings showed that high expression of the Aurora A protein was correlated with elevated nuclear grade, low expression of progesterone receptor and positive nodal stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Therefore AURKA plays an essential role in cell cycle. Overexpression and aberrant amplification of AURKA have been observed in several types of cancers, such as cancers of the breast, colon, ovary, and cutaneous melanoma 13 - 16 . Recent studies have shown that AURKA amplification and overexpression are associated with poor prognosis in diverse cancers 17 - 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore AURKA plays an essential role in cell cycle. Overexpression and aberrant amplification of AURKA have been observed in several types of cancers, such as cancers of the breast, colon, ovary, and cutaneous melanoma 13 - 16 . Recent studies have shown that AURKA amplification and overexpression are associated with poor prognosis in diverse cancers 17 - 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Alisertib is a second-generation and highly selective small molecule inhibitor of AURKA. Because aberrant expression of AURKA has been described in a variety of cancers, including breast cancer (41)(42)(43)(44)(45), the potential antineoplastic activity of alisertib is currently under investigation in a several clinical trials in patients with Figure 14. Oxidative stress and alisertib promote down-regulation of AURKA, ciliogenesis, and premature senescence in primary human fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora A has recently been ranked among the top individual genes in terms of their concordance index values with respect to gene expression and survival data in computational modelling of disease prognosis in breast cancer . There are indications of oncogenic transformation activity of Aurora A with shifts from cytoplasmic staining in non‐malignant adjacent breast tissue to both cytoplasmic and nuclear compartments in tumour tissue, suggesting an oncogenic role for nuclear accumulation . Activated phosphorylated Aurora A Thr288 has recently been associated with tamoxifen resistance in ER‐positive breast cancer by phosphorylation of ERα at positions Ser167 and Ser305, leading to shorter recurrence‐free survival .…”
Section: Discussionmentioning
confidence: 99%